HUBUNGAN MOTIVASI DENGAN KEPATUHAN PERAWAT DALAM PENGGUNAAN ALAT PELINDUNG DIRI (APD) DI RUANG RAWAT INAP RUMAH SAKIT TENTARA WIRASAKTI KUPANG - Appolonaris Tomas Berkanis (CHMK HEALTH JOURNAL, 2019)
Background: Nursing professionals are parts of the human resources in the hospital that provide health service and have direct interactions with patients. The health condition of patients demands nurses to provide quality health service. So it is very likely that they are frequently exposed to environment with various ilnesses and are at risk of contamination. The use of personal protective equipment is an effort to create occupational safety and health for nurses in patientwards. Method: This was a quantitative correlational with cross sectional design. Samples were sellected through total sampling technique, resulting in 35 respondents. Result: Based on the result of Fisher’s Exact Statistical test showed a significant relationship of motivation with nurse compliance in using personal protective equipment in patient wards of Wirasakti hospital Kupang (ρ=0.003). Based on this research, it is expected that nurses can raise their awareness to adhere to the use of personal protective equipment in accordance with the standard operational procedure. Wirasakti hospitalKupang need to hold presentation/seminar/training regularly to all nurses about the use of personal protective equipment and healthcare associated infections(HAIs). Key word: Motivation, Compliance, Personal Protective Equipment